Membangun Karakter Rasa Ingin Tahu Siswa dan Peduli Lingkungan Melalui Pembelajaran Berbasis Riset pada Sekolah Alam PKBM Salam - Anjani, Ananda Dewi; Mutia Irma Fatmawati; Zulfa Muthi’a Batrisyia; Orin Permatasari; Sri Marginingsih; Taufik Muhtarom (Indo-MathEdu Intellectuals Journal, 2025)
The challenge of education today is to create a generation that is not only knowledgeable, but also has strong characters, such as curiosity and concern for the environment. However, formal learning often does not provide enough space for exploration and active involvement of students, so that the development of these two characters is hampered. This study aims to build students' curiosity and environmental awareness through research-based learning at the Nature School PKBM Sanggar Anak Alam (SALAM). The research method uses a descriptive qualitative approach with quantitative analysis, with data collected through observation, interviews, and documentation. Character building is carried out through direct exploration of the surrounding natural environment facilitated by research methods. The results of the study showed that research-based learning encourages students to ask questions, conduct experiments, and explore independently, thereby increasing their curiosity. In addition, students demonstrate real actions in protecting the environment, which reflects the development of environmental awareness. This research-based learning proves that students' active involvement in contextual learning can strengthen their positive character, while creating relevant and meaningful learning experiences